The Effect of Pick Up Delivery and Cash On Delivery Through Customer Satisfaction on Company Revenue (Case Study of Goods Delivery Services in Sukabumi City) - Nursaadawiyah, Siti Halifah Nursaadawiyah; Suherman, Acep; Martaseli, Evi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
The rapid growth of e-commerce in Indonesia today has a big role to play in the sustainability of various industries. One of them is the industry in the field of freight forwarding services. Goods-sending services are a practical solution and a supporting service industry needed by people who often use e-commerce as a means of electronic media to carry out buying and selling activities online. this makes the company faced with the threat of increasingly tight competition. This research uses the Descriptive Quantitative Method by collecting data by distributing questionnaires. The number of respondents in this study were 80 employees of goods delivery services in Sukabumi City with an incidental sampling technique. Data analysis techniques in this study using descriptive statistics. The results of this study indicate that Pick Up Delivery does not have a direct and significant effect on Company Revenue but Pick Up Delivery has an indirect and significant effect on company revenue through Customer Satisfaction as a mediating variable and Cash On Delivery has a direct effect on the revenue of goods delivery companies in Sukabumi City without any mediating role from the Customer Satisfaction variable.